Theoretical investigation on the 2e/12c bond and second hyperpolarizability of azaphenalenyl radical dimers: Strength and effect of dimerization - Zhong, Rong-Lin; Xu, Hong-Liang; Sun, Shi-Ling; Qiu, Yong-Qing; Zhao, Liang; Su, Zhong-Min (The Journal of chemical physics, 2013)
An increasing number of chemists have focused on the investigations of two-electron/multicenter bond (2e/mc) that was first introduced to describe the structure of radical dimers. In this work, the dimerization of two isoelectronic radicals, triazaphenalenyl (TAP) and hexaazaphenalenyl (HAP) has been investigated in theory. Results show TAP2 is a stable dimer with stronger 2e/12c bond and larger interaction energy, while HAP2 is a less stable dimer with larger diradical character. Interestingly, the ultraviolet–visible absorption spectra suggest that the dimerization induces a longer wavelength absorption in visible area, which is dependent on the strength of dimerization. Significantly, the amplitude of second hyperpolarizability (γyyyy) of HAP2 is 1.36 × 106 a.u. that is larger than 7.79 × 104 a.u. of TAP2 because of the larger diradical character of HAP2. Therefore, the results indicate that the strength of radical dimerization can be effectively detected by comparing the magnitude of third order non-linear optical response, which is beneficial for further theoretical and experimental studies on the properties of complexes formed by radical dimerization.